Teaching Practice: A Cross-Professional Perspective - Grossman, Pamela; Compton, Christa; Igra, Danielle; Ronfeldt, Matthew; Shahan, Emily; Williamson, Peter (Teachers College record (1970), 2009)
Background/Context: This study investigates how people are prepared for professional practice in the clergy, teaching, and clinical psychology. The work is located within research on professional education, and research on the teaching and learning of practice. Purpose/Objective/Research Question/Focus of Study: The purpose of the study is to develop a framework to describe and analyze the teaching of practice in professional education programs, specifically preparation for relational practices. Setting: The research took place in eight professional education programs located in seminaries, schools of professional psychology, and universities across the country. Population/Participants/Subjects: Our research participants include faculty members, students, and administrators at each of these eight programs. Research Design: This research is a comparative case study of professional education across three different professions--the clergy, clinical psychology, and teaching. Our data include qualitative case studies of eight preparation programs: two teacher education programs, three seminaries, and three clinical psychology programs. Data Collection and Analysis: For each institution, we conducted site visits that included interviews with administrators, faculty, and staff; observations of multiple classes and fieldwork; and focus groups with students who were either at the midpoint or at the end of their programs. Conclusions/Recommendations: We have identified three key concepts for understanding the pedagogies of practice in professional education: representations, decomposition, and approximations of practice. Representations of practice comprise the different ways that practice is represented in professional education and what these various representations make visible to novices. Decomposition of practice involves breaking down practice into its constituent parts for the purposes of teaching and learning. Approximations of practice refer to opportunities to engage in practices that are more or less proximal to the practices of a profession. In this article, we define and provide examples of the representation, decomposition, and approximation of practice from our study of professional education in the clergy, clinical psychology, and teaching. We conclude that, in the program we studied, prospective teachers have fewer opportunities to engage in approximations that focus on contingent, interactive practice than do novices in our other two professions.